Colombian forensic genetics as a form of public science: The role of race, nation and common sense in the stabilization of DNA populations. (December 2015) - Schwartz-Marín, Ernesto; Wade, Peter; Cruz-Santiago, Arely; Cárdenas, Roosbelinda
This article examines the role that vernacular notions of racialized-regional difference play in the constitution and stabilization of DNA populations in Colombian forensic science, in what we frame as a process of public science. In public science, the imaginations of the scientific world and common-sense public knowledge are integral to the production and circulation of science itself. We explore the origins and circulation of a scientific object – 'La Tabla', published in Paredes et al. and used in genetic forensic identification procedures – among genetic research institutes, forensic genetics laboratories and courtrooms in Bogotá. We unveil the double life of this central object of forensic genetics. On the one hand, La Tabla enjoys an indisputable public place in the processing of forensic genetic evidence in Colombia (paternity cases, identification of bodies, etc.). On the other hand, the relations it establishes between 'race', geography and genetics are questioned among population geneticists in Colombia. Although forensic technicians are aware of the disputes among population geneticists, they use and endorse the relations established between genetics, 'race' and geography because these fit with common-sense notions of visible bodily difference and the regionalization of race in the Colombian nation.